Relationship between soy productive chain, circular economy, precision agriculture, and no-tillage planting system - Silva, Karoline Arguelho; de Araújo Motomiya, Anamari Viegas; Melo, Isotilia Costa; Ferraz, Diogo; do Nascimento Rebelatto, Daisy Aparecida (Revista Gestão da Produção Operações e Sistemas, 2020)
Despite the relevance of these themes for the soy production chain, No-Tillage System, Precision Agriculture, and Circular Economy (CE) are still little studied jointly in the Brazilian context. Less focus has been given to the relationship between the three concepts so far. For this reason, this paper aimed to analyze the contribution of Precision Agriculture and No-Tillage to the achievement of the CE, through the mapping of soy production. The method used was the literature review of the specialized references and the case study, to demonstrate the possibility of a more sustainable production system in a rural property in the state of Mato Grosso do Sul. The results showed that the application of the CE generated better use of the production residues, in addition to the reduction of agricultural inputs used in the rural property. Consequently, it was found that the application of these concepts made the business more profitable for the rural producer.